2022
DOI: 10.1017/s0266462322000125
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of Overall Survival Extrapolations of Immune-Checkpoint Inhibitors Used in Health Technology Assessments by the French Health Authorities

Abstract: Objectives Extrapolation is often required to inform cost-effectiveness (CE) evaluations of immune-checkpoint inhibitors (ICIs) since survival data from pivotal clinical trials are seldom complete. The objectives of this study were to evaluate the accuracy of estimates of long-term overall survival (OS) predicted in French CE assessment reports of ICIs, and to identify models presenting the best fit to the observed long-term survival data. Methods A systematic review of French assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…To limit the risk of misestimation, we used only the economic evaluations validated by the HAS leading to the exclusion of some IT indications and tested the results in sensitivity analyses. Moreover, a previous study indicated that extrapolation tends to underestimate long-term OS in patients treated with ICIs 25 suggesting that we present here a minimal estimation of the benefit. In addition, extrapolations were carried out using data from results of phase III studies (as these data have the highest internal validity), whereas a large difference may exist between the trial population and treated population with reimbursement, especially regarding performance status and comorbidity indexes.…”
Section: Discussionmentioning
confidence: 91%
“…To limit the risk of misestimation, we used only the economic evaluations validated by the HAS leading to the exclusion of some IT indications and tested the results in sensitivity analyses. Moreover, a previous study indicated that extrapolation tends to underestimate long-term OS in patients treated with ICIs 25 suggesting that we present here a minimal estimation of the benefit. In addition, extrapolations were carried out using data from results of phase III studies (as these data have the highest internal validity), whereas a large difference may exist between the trial population and treated population with reimbursement, especially regarding performance status and comorbidity indexes.…”
Section: Discussionmentioning
confidence: 91%
“…Although using flexible techniques can be helpful in reducing the uncertainty of capturing complex survival hazards, few studies take a full model choice into consideration. A recent systematic review of French health technology assessment (HTA) reports indicated that only one study applied a flexible technique among 11 assessed targeted cancer immunotherapies [ 36 ]. Although using external evidence could be helpful when dealing with immature data [ 17 , 19 ], results generated from the immature data should be carefully considered for decision making because of unaddressed uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…In the original publication of Grumberg et al (2022) a typesetting error occurred in Table 2. The correct Table 2 is reproduced below.…”
mentioning
confidence: 99%